Incorporation of Cyano‐Substituted Aromatic Blocks into Naphthalene Diimide‐Based Copolymers: Toward Unipolar n‐Channel Field‐Effect Transistors. Issue 9 (16th July 2021) - Wei, Congyuan; Xu, Pan; Zhang, Weifeng; Zhou, Yankai; Wei, Xuyang; Zheng, Yuanhui; Wang, Liping; Yu, Gui
Abstract : The unipolar n‐type polymeric semiconductors are crucial for the development of complementary inverters and complementary logic circuits. To achieve this target, the polymer skeleton should be electron‐deficient, which guarantees the energy‐level alignment between the lowest unoccupied molecular orbital energy level of polymeric materials and the work function of electrode, further permitting effective electron injection. Different from the introduction of the sp 2 ‐hybridized nitrogen atoms and fluorine atoms, cyano‐substituted aromatic blocks are synthesized and further copolymerized with naphthalene diimide (NDI) unit, affording a series of copolymers of PNDI‐BTCN, PNDI‐TVTCN, and PNDI‐SVSCN . The photophysical, electrochemical, and thermal properties of all the copolymers are systematically investigated, and their semiconducting performance is studied by fabricating field‐effect transistors and tested under atmosphere. All the polymers exhibit unipolar n‐type semiconducting performance because of the synergetic effect of strong electron‐withdrawing NDI units and cyano‐substituted aromatic blocks. The highest mobility of 0.20 cm 2  V −1  s −1 is obtained. Moreover, theoretical simulation and thin‐film characterization are conducted to reveal the difference in semiconducting performance among the three polymeric materials. Abstract : A series of polymers of PNDI‐BTCN, PNDI‐TVTCN, and PNDI‐SVSCN are synthesized and studied systematically. All the materials behave as unipolar n‐type semiconductors because of the synergetic effect of strong electron‐withdrawing naphthalene diimide (NDI) unit and cyano‐substituted aromatic blocks. Owing to the superior crystallinity and surface morphology, devices based on PNDI‐SVSCN perform the highest mobility of 0.20 cm 2  V −1  s −1 .